Nitrogen effluents from mine sites in Northern Sweden : environmental effects and removal of nitrogen in recipients - Frandsen, Sara; Widerlund, Anders; Herbert, Roger; Öhlander, Björn (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2009)
Godkänd; 2009; 20090828 (sarfra)